2020
DOI: 10.1177/0300060520949404
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the clinical characteristics of 202 patients with liver abscess associated with diabetes mellitus and biliary tract disease

Abstract: Objective Clinical characteristics of patients with pyogenic liver abscess (PLA) of varying etiologies may be different. This study aimed to analyze the clinical characteristics, pathogenic bacteria, treatment, and prognosis of patients with PLA associated with diabetes and biliary disease. Methods Clinical, imaging, and laboratory data from 202 inpatients with PLA were retrospectively analyzed. Results Eighty-eight patients (43.6%) had a history of diabetes, 73 (36.1%) had a history of underlying biliary trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…Data were expressed as number (percentage) or mean ± standard deviation. PCD Percutaneous catheter drainage factors for liver abscess [5,7,[27][28][29][30], and the present study covered a large number of individuals with these risk factors; however, the distribution of patients with these underlying diseases did not differ according to the size of the abscess. The detection rate of colonic lesions by colonoscopic examination also showed no difference according to the size of the abscess.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Data were expressed as number (percentage) or mean ± standard deviation. PCD Percutaneous catheter drainage factors for liver abscess [5,7,[27][28][29][30], and the present study covered a large number of individuals with these risk factors; however, the distribution of patients with these underlying diseases did not differ according to the size of the abscess. The detection rate of colonic lesions by colonoscopic examination also showed no difference according to the size of the abscess.…”
Section: Discussionmentioning
confidence: 76%
“…Regarding the size of the liver abscess, demographic and isolated microorganisms did not differ according to the size of the liver abscess. Underlying malignancy, DM, biliary tract diseases, and liver cirrhosis are known risk factors for liver abscess [ 5 , 7 , 27 30 ], and the present study covered a large number of individuals with these risk factors; however, the distribution of patients with these underlying diseases did not differ according to the size of the abscess. The detection rate of colonic lesions by colonoscopic examination also showed no difference according to the size of the abscess.…”
Section: Discussionmentioning
confidence: 99%
“…Liver abscesses, either pyogenic or amoebic, remain a significant cause of morbidity and mortality in tropical countries (19). Morbidity and mortality are highly affected by several factors such as the presence of diabetes, which is accredited to low immunity, biliary disease, and type of organism, a recently published meta-analysis, Chan et al concluded that klebsiella pneumoniae has lower mortality than non-klebsiella pneumoniae pyogenic liver abscess (40)(41)(42). Liver abscess has been even more common recently due to the increasing biliary interventions (20).…”
Section: Discussionmentioning
confidence: 99%
“…The pathophysiology of KP infection associated with DM is incompletely understood. However, the susceptibility of infection appears to be strongly associated with hyperglycemia Decreased mobilization of polymorphonuclear leukocytes, chemotaxis, and phagocytic activity may occur during hyperglycemia ( 17 19 ).…”
Section: Discussionmentioning
confidence: 99%